Magnitude of postpartum hemorrhage and associated factors among women who gave birth in Ethiopia: a systematic review and meta-analysis - Tadesse Tolossa; Getahun Fetensa; Edgeit Abebe Zewde; Merga Besho; Tafese Dejene Jidha (BMC, 2022)
Plain Language summary Postpartum hemorrhage (PPH) is the leading cause of maternal mortality and morbidity worldwide, particularly in resource-limited countries such as Ethiopia. Findings from a few studies were inconsistent and inconclusive. Therefore, this study aimed to estimate the pooled magnitude of PPH and factors associated with PPH among women who gave birth in Ethiopia. Electronic databases such as Medline, Pub Med, Cochrane library, the Web of Science, and Google Scholar were used to search for articles. Data were extracted using a standardized data extraction checklist and the analyses were conducted using Stata version 14. The Cochrane Q test statistic and I 2 statistics were used to assessing heterogeneity. To estimate the pooled magnitude of postpartum hemorrhage, a random-effects model was fitted. Association between PPH and independent variables was reported in odds ratio (OR) with 95% confidence interval (CI). The pooled magnitude of PPH in Ethiopia was 11.14% (95% CI 7.21, 15.07). The current meta-analysis revealed that lack of antenatal care follow-up (ANC) (OR = 6.52, 95% CI 2.87, 14.81), being multipara (OR = 1.88, 95% CI 1.25, 2.85), and having the previous history of PPH (OR = 7.59, 95% CI 1.88, 30.55) were found to be significantly associated with PPH. In Ethiopia the magnitude of PPH was high, and lack of ANC follow-up, being multipara, and having the previous history of PPH were risk factors for postpartum hemorrhage. Thus, improving antenatal care follow-up is needed to decrease the magnitude of postpartum hemorrhage.